SHАKIR SULЕYMАN IS AN ACTIVE REPRESENTATIVE OF THE TURKESTAN YOUTH SERVED THE DEVELOPMENT OF THE COUNTRY (Scientific journal of the Fergana State University, 2023)
The main purpose of this article is to highlight the contribution of Sh. Suleiman to the development of Turkestan throughout his life. With his rich works and actions, he left a special mark in the social and cultural life of the 20-30s of the twentieth century, in particular, in Uzbek literature. Scientific literature, sources and archival documents are involved in the coverage of the article. The data is compared and structured. Articles by Shakir Suleiman are analyzed. He took an active part in raising funds for the education of Turkestan youth abroad and the unification of talented youth. He also studied in the central city of Russia. Contributed to the development of Uzbek science. However, he became a victim of repression as a result of the repressive policies of the Soviet government.